'We Did Many Projects Together': Boundary-Spanning Strategies of Councillors in Rural Ghana. (April 2023) - Sabbi, Matthew
A thematic gap in decentralization research is how rural councillors with limited political scope assert agency in rural transformation processes. Analysis of councillors' strategic interfaces with local organisations and international agencies outside the elected councils explores how they construct access to resources for rural development. Drawing on fieldwork in rural Ghana, the article demonstrates how creative boundary-spanning links councillors to different structures of rural governance and development intervention outside the remit of the district council. Clearly emergent from this study is that the cross-boundary collaborations create privileged access to outside resources and support for local political action but with significant political and economic consequences for councillors. These collaborative engagements offer a wider framework to understand councillors' individual agency for rural transformation beyond conventional analyses of state-led or bottom-up development planning and the dominant critique of external intervention.